Musiketnologi og musikhistorie - Kirkegaard, Annemette (Danish Yearbook of Musicology, 1998)
Ethnomusicology and Music History The point of this essay is to stress and demonstrate – making use of theories from interdisciplinary studies – the extent to which musicology and ethnomusicology can and should work together. The article insists on Bruno Nettl’s three criteria for defining ethnomusicology (comparison, study in or as culture, and the outsider perspective), and discusses the basis for applying ethnomusicological theory and methods to discourse on processes of musical change. The author emphasizes that even though the domain of ethnomusicology can obviously be used as a means of studying a particular cultural system and its reaction to change – as opposed to historical musicology, which works with the content of that change –, ethnomusicology also gives a unique perspective to the analysis. Like the American musicologists Joseph Kerman and Leo Treitler, the author finds that ethnomusicological theories and methods can challenge the evolutionist canon of traditional musicology; in other words, that the discourse of the so-called ethnographic present puts the object of study (the interpretation and evaluation of the interviewed) in focus instead of trying to relate the subject to the canon.